ANALISIS MAJAS PADA CERITA PENDEK “RAIN” KARYA NURILLAIYAH - Robayani, Anisa; Mustika, Ika; Permana, Indra (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
This research was carried out because it was found in the short story "Rain" by Nurillaiyah which had many masters in each series of stories written. Understanding of the reader in understanding the meaning of a reading that is still lacking in the background of the implementation of this style or language analysis. So in this study the researchers took two formulations of the problem, namely what meaning is implied in the short story "Rain"? and what style of language is used in the short story "Rain"? The purpose of this study is to analyze the majas in the short story "Rain" so that the reader is able to distinguish the types of majas, the meaning of the majas and appreciation of the majes outlined by the writer. In this study, researchers used a qualitative descriptive research method to analyze the composition contained in the short story "Rain", this research was conducted by reading the short story first, then analyzing and marking which text is included in the paper, then from the data that has been analyzed researchers found various kinds of majas in the short story "Rain", namely there are comparative forms, including personification, metaphor, allegory, hyperbole, sinekdok and simile, affirmation forms including repetition, rhetoric, asindeton, pleonasme, enumeration, and contradictory forms namely paradox and satire majesty namely innuendo. The conclusion is that this research is expected to be able to add insight in understanding understanding of discourse in terms of semantic knowledge.